FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - VIRA SAGITA GARNISA; FUNG NJIT TJHAI (E-Jurnal Akuntansi TSM, 2021)
The purpose of this study is to examine an empirical evidence about the influence of firm size, return on assets, leverage, capital intensity, sales growth, majority shareholding and audit quality to tax avoidance. The population of this study are manufacture companies listed in Indonesia Stock Exchange from 2015-2018, with 3 years observation period. The data was obtained from Indonesia Stock Exchange website. The sample of this research are 54 companies which obtained by using purposive sampling. The empirical result indicates that the return on assets, capital intensity and audit quality have influence to tax avoidance and firm size, leverage, sales growth and majority shareholding does not have influence to tax avoidance.